2005
DOI: 10.1681/asn.2004030236
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Cellular Effects of Direct Maxacalcitol Injection into Parathyroid Gland in Uremic Rats

Abstract: The most important etiological factors of resistance to medical treatments for secondary hyperparathyroidism are the decreased contents of the vitamin D receptor (VDR) and Ca-sensing receptor (CaSR) in parathyroid cells and a severely swollen parathyroid gland (PTG) as a result of hyperplasia. The effects of direct maxacalcitol (OCT) injection into PTG in terms of these factors were investigated in this study. The PTG of Sprague-Dawley rats that were 5/6 nephrectomized and fed a high-phosphate diet were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 33 publications
(23 reference statements)
3
32
0
1
Order By: Relevance
“…In this study we confirmed from the laboratory data that this animal model produces uremia-induced SHPT, agreeing with a previous study involving a model of advanced SHPT, in which PTH synthesis and secretion, and PTC proliferation activity, were very high, and levels of VDR and CaSR in the PTG were very low [6]. Moreover, it should be noted that significant differences in terms of changes in the levels of serum intact PTH, Ca 2+ and P between the CAL and OCT groups were not observed, indicating that differences in gene expression levels were independent of these biochemical changes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study we confirmed from the laboratory data that this animal model produces uremia-induced SHPT, agreeing with a previous study involving a model of advanced SHPT, in which PTH synthesis and secretion, and PTC proliferation activity, were very high, and levels of VDR and CaSR in the PTG were very low [6]. Moreover, it should be noted that significant differences in terms of changes in the levels of serum intact PTH, Ca 2+ and P between the CAL and OCT groups were not observed, indicating that differences in gene expression levels were independent of these biochemical changes.…”
Section: Discussionsupporting
confidence: 92%
“…This procedure has been described in detail elsewhere [6]. The Animal Studies Committee of Wakayama Medical University approved all experimental animal protocols.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In rat models, several studies have been unable to find evidence for programmed PC death in normal or hyperplastic parathyroid tissue (19 -21). There are no known stimuli for apoptosis in the PC (22), although an effect of vitamin D has not been excluded completely (23)(24)(25)(26). The evidence for induction of massive apoptosis by calcitriol still is contradictory, however.…”
Section: Can Parathyroid Hyperplasia Be Arrested or Reversed?mentioning
confidence: 99%
“…The changes were detectable within 4 d and could have resulted only from apoptosis. Recently, a significant induction of apoptosis was demonstrated by 22-oxa-1,25-dihydroxyvitamin D 3 , maxacalcitol injection directly into the parathyroid glands of uremic rats by Shiizaki et al (26). The process of apoptosis was assessed directly by the transferase-mediated dUTP nick-end labeling method for identification of DNA fragmentation.…”
Section: Can Parathyroid Hyperplasia Be Arrested or Reversed?mentioning
confidence: 99%